Accountants’ perception of AI and their willingness to utilize it - van Ijzendoorn, Laura (My University, 2024)
Artificial intelligence has revolutionised many industries and could evolve the accountancy industry as well. However, the traditional role of the accountant could be risked by doing so, as the security of their jobs is becoming a concern and the need for accountants to increase their skills is being called out. Current literature Current research focuses on what AI can do for the accountancy sector. However, literature should look at the accountant and whether they are willing to accept such change, or if they are ready for it. This thesis aims to gain insight into the accountant’s perceived potential of AI and their willingness to utilize it, by asking the following research question: How do accountants perceive the potential of using AI in different accounting tasks and how does the context influence their willingness to utilize AI? To research this question a case study has been conducted. The data for this case study has been collected through semi-structured interviews, based on the Task-Technology Fit framework by Goodhue and Thompson. In total 11 accountants from Govers Accountants/Adviseurs have been interviewed. The organisation is starting to look into how they might apply AI. The results show that accountants support the idea that AI can become a tool in their daily work. However, having AI completely take over tasks leaves mixed reactions. Furthermore, increasing quality, efficiency and delivering added value to clients are seen as the positive consequences of AI use although, there is still worry regarding the explainability and dependability of AI due to a lack of knowledge and guidance from laws & regulations. From a practical point of view, this research shows a need for enhancing accountants’ knowledge of AI through training, where concrete and practical examples will be key to making the added value that AI will bring clear. In addition, there is a need to keep up-to-date with the technological developments in the market, possibly through collaborations with other organisations. These recommendations aim to assist accountancy organisations in becoming aware of what tasks AI could perform and what triggers stakeholders into utilising AI in the workplace, so that the AI implementation is successful and the AI is fully utilised. From a theoretical perspective, this research contributes to the literature by proposing variables that influence the willingness of accountants to utilize AI. The research advocates a need for clear regulations on the use of AI in accountancy, as well as proactive measures regarding the current lack of knowledge regarding AI.
Keywords: AI, Accountancy, utilization, Task-Technology Fit.